EDUKASI DAN PENERAPAN BIOPORI (LUBANG RESAPAN) DI RUMAH WARGA - Wafa Nur Shodiqoh; Kanza Putri; Ririn Widyasari; Ika Puji Eviyanti; Asti Wulan Ardelia; Indanah Indanah; Fida Maisa Hana (Universitas Muhammadiyah Kudus, 2024)
Kaliwungu Village faces two primary issues: high population density with diminishing water absorption areas and uncontrolled waste accumulation. This results in waterlogging and environmental health problems. To address these concerns, the KKN team implemented a biopore installation program. The program involved site surveys, socialization, and biopore installations in four locations (RW 06, 02, 05, and 08). Despite encountering rock formations during drilling, the team successfully installed PVC pipes filled with organic waste for composting. The program yielded positive impacts, including increased awareness of organic waste management, reduced waterlogging, and improved environmental quality. For sustainability, regular biopore maintenance, community education, and periodic evaluations are necessary